2012
DOI: 10.1084/jem.20120904
|View full text |Cite
|
Sign up to set email alerts
|

The coding genome of splenic marginal zone lymphoma: activation of NOTCH2 and other pathways regulating marginal zone development

Abstract: Notch2 mutations represent the most frequent lesion in splenic marginal zone lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
347
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(371 citation statements)
references
References 62 publications
12
347
2
2
Order By: Relevance
“…Similar activating mutations have been recently described in splenic marginal zone lymphomas and in NOTCH1 in aggressive CLL and MCL (37,38). These findings prompted us to expand the study of NOTCH2 and NOTCH1 mutations in MCL and found their presence in 5.2% and 4.7% of the tumors, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar activating mutations have been recently described in splenic marginal zone lymphomas and in NOTCH1 in aggressive CLL and MCL (37,38). These findings prompted us to expand the study of NOTCH2 and NOTCH1 mutations in MCL and found their presence in 5.2% and 4.7% of the tumors, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, NOTCH1 mutations have been found in CLL (18,26) whereas NOTCH2 is mutated in splenic marginal zone lymphomas (37,38); however, none of these tumors carry mutations in both NOTCH genes as observed in MCL. In addition, MLL2 and MEF2B mutations are shared with DLBCL (31-33) but are uncommon in CLL, whereas MCL has frequent mutations of ATM and BIRC3 that are also frequent in CLL (39) but uncommon in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases (40%; 95% CI: 19-64%; n = 6/15) utilized the IGHV4-34 gene and expressed mutated immunoglobulins (80%; 95% CI: 54-93%; n = 12/15) (Table SI). Overall, this clinical picture is consistent with that of the CBL-MZ cases described by Xochelli et al (2014).Mutually exclusive lesions of genes belonging to the physiological programme of MZ differentiation occurred in 37% (95% CI: 18-61%; n = 6/16) of CBL-MZ cases (Fig 1), a prevalence that did not significantly differ from that observed in SMZL (P = 0Á154) (Rossi et al, 2012). NOTCH2 mutations occurred in 13% (95% CI: 2-37%; n = 2/16) of cases, MYD88 mutations in 25% (95% CI: 9-49%; n = 4/16), and TNFAIP3 and CD79B mutations in 6% (95% CI: 0-30%; n = 1/16) each (Fig 1).…”
supporting
confidence: 87%
“…We were not able to assess LOH for these 2 cases. Recent work has identified truncating SPEN and NOTCH2 mutations in splenic marginal zone lymphoma (21). Of note, none of the SPEN mutations reported had evidence for loss of the wild-type allele, similarly arguing against a simple lossof-function mechanism for SPEN mutation in this cancer type.…”
Section: Resultsmentioning
confidence: 99%